Community Characteristics and the Geographic Distribution of Intimate Partner Violence: A Partial Test of Social Disorganization Theory - McDowell, Molly (Journal of interpersonal violence, 2023)
Shaw and McKay’s social disorganization theory has provided a framework to examine the relationship between community-level structural variables and neighborhood crime. Although empirical support for the theory has been widely demonstrated using property and violent crime data, the body of literature examining the theory’s applicability to intimate partner violence (IPV) is more limited. Further, much of the existing literature in this area applies the theory’s macro-level variables to individual outcomes instead of assessing community effects. Using negative binomial regression to analyze incident data from the Austin (TX) Police Department and demographic information from the United States Census Bureau, this study assesses the relationship between concentrated disadvantage, racial/ethnic heterogeneity, residential instability, and the geographic distribution of IPV incidents in a major U.S. city with no racial or ethnic majority. The independent variables of interest were constructed using principal axis factoring, and a spatial lag variable was included in the model to control for spatial clustering. The analysis showed that concentrated disadvantage was significantly, positively associated with annual counts of IPV incidents in neighborhoods, as was the control variable total crime reports. These results demonstrate that the geographic distribution of IPV is influenced by community factors. They underscore the importance of considering community-wide prevention and intervention efforts in tandem with individual services to those impacted by IPV.